Synchronization of Green Algae by Light and Dark Regimes for Cell Cycle and Cell Division Studies - Hlavová, Monika; Vítová, Milada; Bišová, Kateřina (Methods in molecular biology, 2016)
A synchronous population of cells is one of the prerequisites for studying cell cycle processes such as DNA replication, nuclear and cellular division. Green algae dividing by multiple fission represent a unique single cell system enabling the preparation of highly synchronous cultures by application of a light-dark regime similar to what they experience in nature. This chapter provides detailed protocols for synchronization of different algal species by alternating light-dark cycles; all critical points are discussed extensively. Moreover, detailed information on basic analysis of cell cycle progression in such cultures is presented, including analyses of nuclear, cellular, and chloroplast divisions. Modifications of basic protocols that enable changes in cell cycle progression are also suggested so that nuclear or chloroplast divisions can be followed separately.
Keywords: buněčné dělení; DNA Replication; Staining and Labeling; DNA, Plant; Cell Culture Techniques; Chloroplasts; světlo; replikace DNA; buněčný cyklus; barvení a značení; Cell Cycle; Chlorophyta; frakcionace buněk; DNA rostlinná; Chlamydomonas reinhardtii; Light; Photoperiod; Cell Fractionation; fotoperioda; buněčné kultury; Cell Division; chloroplasty